Credit Portfolios, Credibility Theory, and Dynamic Empirical Bayes. (26th November 2012) - Lai, Tze Leung
Abstract : We begin with a review of (a) the pricing theory of multiname credit derivatives to hedge the credit risk of a portfolio of corporate bonds and (b) current approaches to modeling correlated default intensities. We then consider pricing of insurance contracts using credibility theory in actuarial science. After a brief discussion of the similarities and differences of both pricing theories, we propose a new unified approach, which uses recent advances in dynamic empirical Bayes modeling, to evolutionary credibility in insurance rate-making and default modeling of credit portfolios.